Land-use, transport choice and population health: opportunities for highly motorized and rapidly motorizing countries - Mark Stevenson (9353) (2015)
The presentation will highlight the population health effects arising from land-use changes and public policy initiatives that lead to changes in transport mode share for six international cities namely, Melbourne, Beijing, Delhi, London, Copenhagen and New York. The findings demonstrate that policies encouraging optimal land-use for active transport combined with provision of infrastructure that reduces the risk of injury for vulnerable road users (in association with road safety interventions) can produce considerable population health benefits across both chronic disease and road trauma. Without such infrastructure, however, increases in road trauma are likely, especially within highly motorised cities. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.100